Theoretical study on a dual-beam model for detection of track/bridge frequencies and track modulus by a moving vehicle. (1st October 2021) - Yang, Y.B.; Shi, K.; Wang, Zhi-Lu; Xu, Hao; Wu, Y.T.
Highlights: Theory for detecting dual frequencies and track modulus by using VSM. Derive closed-form solutions for the vehicle and contact-point responses. Contact-point spectrum performs better as it is free of the vehicle frequency. Identify track modulus from the first "plus" frequency of the double beams. Parametric study for factors affecting the technique. Abstract: A theory is presented for retrieving the track/bridge frequencies and track modulus from an instrumented vehicle moving over a dual-beam model to simulate the track-bridge system. The dual beams are connected by uniform spring-dashpot units to simulate the effects of sleepers and ballast, etc. Based on the dual-beam model, the response of the vehicle is firstly derived in closed form, along with that for the vehicle-track contact point . The dual frequencies solved relate to the track and bridge frequencies. Compared with the vehicle spectrum, the contact-point (CP) spectrum is superior in that it is free of the vehicle and driving frequencies. Using the first "plus" frequency of the dual-beam system, the track modulus can be computed by a simple formula. The proposed technique is numerically validated against the key parameters involved. It is concluded that: (1) the first "plus" frequency can be retrieved from the contact-point spectrum as an outstanding peak; (2) track irregularity has an adverse, but tolerable, effect on retrieval of track modulus; (3) as a trade-off between efficiency and accuracy, the vehicle is suggested to move at a moderate speed; and (4) the proposed technique may be affected by track damping, but remains good for tracks with infinite length.